The Concept of the Manners of Seeking Knowledge According to Imam Al-Ghazali and its Relevance for Contemporary Islamic Education: A Literature Review - Wijaya Wijaya (Journal of Noesantara Islamic Studies, 2025)
The Palembang Sultanate's strategic position along trade routes, and its political stability fostered a dynamic intellectual climate that combined religious studies, Sufi traditions, and local literary creativity. This study aims to analyze the role of the Palembang Sultanate as a center of Islamic education and as a contributor to the development of Malay-Islamic literature during this formative period. The research employs a qualitative historical approach with textual and archival analysis of manuscripts, royal decrees, and scholarly treatises compiled by Palembang scholars. The findings indicate that the Sultanate's intellectual institutions, particularly the royal madrasahs and Sufi pondoks, served as important platforms for integrating Islamic jurisprudence, theology, and mystical knowledge into the region's cultural fabric. The resulting literary works, including didactic poetry, commentaries, and Sufi prose, reflect a synthesis between Arab-Islamic epistemology and local Malay expressions. This conclusion highlights that the Palembang Sultanate functioned not only as a political entity but also as a center of Islamic intellectual and literary transformation that significantly shaped regional religious identity.